2015
DOI: 10.1530/erc-15-0408
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic thyroiditis and BRAF V600E in papillary thyroid carcinoma

Abstract: It has been reported that papillary thyroid carcinoma (PTC) with chronic lymphocytic thyroiditis (CLT) is less associated with extrathyroidal extension (ETE), advanced tumor stage and lymph node (LN) metastasis. Other studies have suggested that concurrent CLT could antagonize PTC progression, even in BRAF-positive patients. Since the clinical significance of the BRAF mutation has been particularly associated with conventional PTC, the purpose of this study was to determine the clinical significance of CLT acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 41 publications
9
28
1
Order By: Relevance
“…Therefore, we did not separately Journal of Surgical Oncology present ETE as microscopic and gross. And previous studies have shown that the coexistence of CLT is negatively associated with ETE, advanced stage, LN metastasis, and recurrence in PTC patients [19,[32][33][34]. Because this study was a retrospective study, the analyses were conducted based on pathologic reports.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we did not separately Journal of Surgical Oncology present ETE as microscopic and gross. And previous studies have shown that the coexistence of CLT is negatively associated with ETE, advanced stage, LN metastasis, and recurrence in PTC patients [19,[32][33][34]. Because this study was a retrospective study, the analyses were conducted based on pathologic reports.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, only few studies reported a worse prognosis of PTC associated with CLTI, but the great majority agree with the hypothesis that the presence of CTLI may lead to a better prognosis or not influence the clinical outcome of PTC [6,13,17,23]. Kim et al, in a study aimed to define the role of CLTI according to BRAF V600E mutation status in a cohort of PTC patients, concluded that CLTI was an independent predictor for low prevalence of both extra-thyroidal extension and central compartment nodal metastases, regardless BRAF mutation status [24]. Nevertheless, higher prevalence of multifocal or bilateral lesions was reported in TC patients with coexisting CLTI [24] and recently Iliadou el al [25] showed that children and adolescents with CLTI presented more frequently familial PTC, even if no differences in outcome were found with respect to the presence of CLTI.…”
Section: Thyroid Cancer and Autoimmunity: Epidemiological And Clinicamentioning
confidence: 95%
“…Kim et al, in a study aimed to define the role of CLTI according to BRAF V600E mutation status in a cohort of PTC patients, concluded that CLTI was an independent predictor for low prevalence of both extra-thyroidal extension and central compartment nodal metastases, regardless BRAF mutation status [24]. Nevertheless, higher prevalence of multifocal or bilateral lesions was reported in TC patients with coexisting CLTI [24] and recently Iliadou el al [25] showed that children and adolescents with CLTI presented more frequently familial PTC, even if no differences in outcome were found with respect to the presence of CLTI. In this regard, it should finally be noted that TC histotypes with a worse prognosis (PDTC, ATC) are characterized by a very reduced lymphocyte infiltration [26].…”
Section: Thyroid Cancer and Autoimmunity: Epidemiological And Clinicamentioning
confidence: 99%
See 1 more Smart Citation
“…Whether thyroid autoimmunity represents a risk factor for cancer is still a matter of debate [10,11]. Some authors suggest that chronic thyroiditis might protect againts aggressive forms of papillary carcinoma (including BRAF positive patients since the mutation is frequently found in typically papillary forms) [12]. Others suggested that the inflammatory environment induced by the immune process is a trigger for genetic aberrations as seen in hOGG1 loss of heterozygosity (the gene repairs the DNA from free radical-induced oxidative stress) [13].…”
Section: Introductionmentioning
confidence: 99%